Educação, escola e prisão: o espaço de voz de educandos do Centro de Ressocialização de Rio Claro/SP - Campos, Aline (2015)
Studies on the humanization of prisons and on school education as a right have intensified in recent years and helped to ensure the implementation of education for people on restricted situation and deprivation of liberty. In São Paulo State, the Resocialization Centers (CR) are created between 2000 and 2005 in order to contribute to the humanization of penalties through the transformation of the prison reality. Configured as small and minimum security units, these centers show several aspects that differ from "traditional units , as an example, the labor and school education supply for most inmates. Intending to contribute to enlarge the discussions about the school education in places of deprivation and restriction of liberty, this study aimed to answer the following research question: Which are the meanings that people in situation of liberty deprivation in a Resocialization Center assign to education, school and prison? To meet the proposed question, the main objective was to understand the meanings assigned to education, school and prison by men in situation of liberty deprivation in the Resocialization Center of Rio Claro, SP. Relying on qualitative approach to educational research and using the theoretical and methodological tools of participative research, the data were collected through conversation circles with 11 collaborators, records on field diary and considerations written by the collaborators. The systematic reading of the data allowed the identification of meaning units, which were then grouped into major themes from where emerged two central analysis focus. The first focus Prison: the voices of the CR inmates who experienced other prison models provided the opportunity to understand that the collaborators mean the prison as a place of punishment and dehumanization, where rarely they witness actions that aim to contribute to the (re)socialization. The CR, in its turn, are identified as more worthy prison units to serve the sentence, but that need to be improved. The second focus Education: voices of young and adults students, once escaped from school provided the opportunity to understand that education is an ongoing process that is not restricted to educational institutions. The school is pointed out as an uninteresting space and decontextualized from the realities, however, the students point to school education as an asset that provides better living conditions. School education in prison is an opportunity to the resumption of the studies and a possibility of establishing new life projects, however, have been reproducing the exhaustion of the education system. The research results reveal elements that support the importance of an education based on the liberating principals for people in situations of restriction and deprivation of liberty and show unit s teachers and workers as fundamental tools for the transformation of the prison reality. With no intention to show receipts or absolute truths, the study brings contributions to the discussion about research methodologies for places of liberty deprivation and to the reflection on the school practice in these places.